Irena's children : a true story of courage by Tilar J. Mazzeo - Mazzeo, Tilar J. (Margaret K. McElderry Books, 2016)
Tells the story of Irena Sendler, a courageous Polish woman who saved 2,500 Jewish children in Nazi-occupied Poland during World War II.